2021
DOI: 10.1108/scm-06-2020-0263
|View full text |Cite
|
Sign up to set email alerts
|

Restraining forces and drivers of supply chain collaboration: evidence from an emerging market

Abstract: Purpose This paper aims to investigate how restraining forces and driving forces impact SC collaboration in the context of Nigeria. Design/methodology/approach A qualitative approach was adopted. Using semi-structured interviews, data was obtained from manufacturers and third-party logistics providers in Nigeria’s food and beverage sector. The data was analysed using the thematic analysis method. Findings Interesting findings were revealed regarding how some underlying forces impact SC collaboration. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 123 publications
(195 reference statements)
1
10
0
Order By: Relevance
“…Further, a number of studies highlight the requirement to explore and expand the literature considering the nascent stage of emerging market literature (Orji et al. , 2020; Oyedijo et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, a number of studies highlight the requirement to explore and expand the literature considering the nascent stage of emerging market literature (Orji et al. , 2020; Oyedijo et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The previous literature that focusses on the Sustainable Supply Chain (SSC) has advised exploring the business practices and management of the supply chain in emerging markets (Koberg and Longoni, 2019). Oyedijo et al (2021) reported several emerging market issues, including political instability, inadequate infrastructure, lack of transparency and an inefficient regulatory system. The authors highlight that solutions of the developed economy will not work on the emerging markets.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Bureaucratic decision-making processes and procedures might be simplified or automated to accomplish this. A number of Oyedijo, Francois Koukpaki, Kusi-Sarpong, Alfarsi, and Yang [33] have built on the concept of cooperation/collaboration by claiming that if all actors in the supply chain are closely coupled and "work as one," fewer difficulties with the process, supply, demand, and control of a product may be anticipated. The next step in an integration plan is to integrate management information systems upstream to distributors and downstream to consumers, once operational and institutional integration have been completed.…”
Section: Fig 2 Ten Uncertainty Management Approachesmentioning
confidence: 99%
“…Mahmud et al (2021) describe informationrelated and communication-related barriers as two broad categories of barriers to supply chain collaboration. Information-related barriers deal with aspects such as reluctance of actors to share information and communication-related ones are lack of communication as well as poor connectivity (Oyedijo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%